PARTAI POLITIK DALAM PEMENANGAN SUYATNO DAN JAMILUDIN PADA PEMILIHAN KEPALA DAERAH KABUPATEN ROKAN HILIR TAHUN 2015 - Arimi "; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Political parties as an icon of democracy is an organization engaged in the political process. Political parties have the goal of conquering power or take part in a launch power. For that victory in local elections became a very important thing obtained as the achievement of the objectives of political parties.This research was conducted in the District Rokan Hilir. The data used in this study is Primary data and secondary data. Data collection through in-depth interviews and documentation. This study uses qualitative descriptive method because the retrieval of data from informants depth interviews of informants related. So that the problem in this case is How Political Parties in Victory Suyatno and Jamiludin in local elections Rokan Hilir 2015.The results of this study are the political parties have an enormous influence on the award-Jamiludin Suyatno in Rokan Hilir. It can be seen from the performance of the party and the winning team always brings out creativity in conducting political campaign. In addition to campaign actively is also the most effective efforts are decisive victory Suyatno-Jamiluddin in Rokan Hilir in the general election of Regional Head in the title 2015. Political Parties is a highly effective tool in the campaign in the county Regional Head of Rokan Hilir. That's because the political parties were able to encourage people Rokan Hilir to steer voters in mmilih Suyatno-Jamiludin by optimizing campaigns and external network utilization.Keywords: Political Parties, the Victory, Regional Head Election